Evaluation of the effect of information integration in displays for ICU nurses on situation awareness and task completion time: a prospective randomized controlled study - Koch, Sven H.; Weir, Charlene; Westenskow, Dwayne; Gondan, Matthias; Agutter, Jim; Haar, Maral; Liu, David; Görges, Matthias; Staggers, Nancy (International journal of medical informatics, 2013)
Objective - The study measured whether nurses’ situation awareness would increase and task completion time decrease when they used an integrated information display compared to traditional displays for medication management, patient awareness and team communication. - Setting - The Burn Trauma Intensive Care Unit (BTICU) at the University Hospital, University of Utah Health Science Center, Salt Lake City, Utah, USA. - Participants - 12 experienced BTICU nurses. - Measures - Situation awareness (accuracy of the participants’ answer) and task completion time (response time from seeing the question to submitting the answer) were measured using paper prototypes of both displays. - Study design - Counter-balanced (on display order), repeated-measures design. - Main results - Nurses had a higher situation awareness when using the integrated display, with an overall accuracy of 85.3% compared to 61.8% with the traditional displays (odds ratio 3.61, P<.001, 95% CI=2.34…5.57). Task completion times were nearly half with integrated displays compared to traditional displays (median 26.0 and 42.1s, hazard ratio 2.31, P<.001, CI=1.83…2.93). - Conclusions - An integrated ICU information display increased nurses’ situation awareness and decreased task completion time. Information integration has the potential to decrease errors, increase nurses’ productivity and may allow nurses to react faster to a patient's clinical needs. Bidirectional device communication is needed for these displays to achieve full potential in improving patient safety.
Gesehen am 02.06.2022